The investigation of microporous structure and fluid distribution mechanism in tight sandstone gas reservoirs: A case study on the second member of Xujiahe gas reservoirs in Yuanba area - Guo, Tonglou; Fu, Dongyu; Xiong, Liang; Wang, Yongfei (Frontiers in Energy Research, 2022)
Tight sandstone reservoir is characterized by ultra-low porosity, complex microporous structure and water residues, which shows different gas storage and transport mechanism from conventional reservoirs. Therefore, effective development of tight sandstone gas reservoirs is faced with technical challenges. Microporous structures, distribution mechanism of fluid is a basic issue in gas reservoir evaluation. In this work, we take gas reservoir in the 2nd member of Xujiahe Formation in Yuanba area as an example to analyze the microscopic feature of pore structure and fluid distribution. The three-dimensional digital core has been applied to represent the real microporous structure. Specifically, a dual-scale digital core reconstruction method based on SEM and casting slice images has been proposed. Ultimately, the mechanism of distribution, mode of occurrence of water residues in tight sandstone reservoirs has been simulated and quantitatively analyzed. The results show that the water residues could been visualized and categorized into three modes, water mass in corner, water film on surface, and water column in throat. The water residues could cause dramatic influence on pore structures, active pore size could be decreased with rising residual water saturation, the magnitude fell by over 50%. In addition, grain size would affect the distribution of water residues, which shows different percentage in medium and fine sand. Pore connectivity is another characteristic factor to describe the microporous structures. In this study, cluster marking algorithm has been applied to obtain the pore connectivity in tight sandstone with different grain size. In medium sand, the pore connectivity is dramatically decreased with rising water saturation, the downward trend become slower when water saturation reaches to 60%. Compared to fine sand, the tendency variation appears when water saturation reaches to 40%. This paper provides an applicable method to reveal the micro-scale reservoir properties and fluid distribution mechanisms in tight sandstone gas reservoirs.